COVID-19: Assessing impacts and policy responses for food and nutrition security - Swinnen, Johan; McDermott, John (International Food Policy Research Institute, 2020)
COVID-19 has severely disrupted our lives, jeopardized the well-being of billions of people, and raised the specter of a global food crisis, all in just a few months. The huge impact expected on the world’s economy and on global food security has been described in dramatic terms. The World Bank forecasts that the global economy will shrink by more than 5%, which would be the deepest recession since the Second World War. IFPRI researchers estimate that, in the absence of strong interventions in developing countries, the number of people in extreme poverty could increase by up to 150 million. The World Food Programme’s executive director, David Beasley, has warned that the world is “not only facing a global health pandemic but also a global humanitarian catastrophe,” and that, without action, COVID-19 could lead to “multiple famines of biblical proportions.” Lawrence Haddad, executive director of GAIN, lamented that the coming food and nutrition crisis is not only biblical but “on steroids, and across generations.”